Cerebral blood flow in the paracentral lobule is associated with poor subjective sleep quality among patients with a history of methadone maintenance treatment - Sun, Jiaxue; Lu, Yi; Kong, Deshenyue; Lin, Wenhua; Du, Jinze; Wang, Guangqing; Ma, Xingfeng; Li, Congbin; Wang, Kunhua; Zhu, Mei; Xu, Yu (Frontiers in Neurology, 2024)
Introduction Sleep disorders are prevalent and significant among individuals receiving methadone maintenance treatment (MMT), adversely affecting their quality of life and treatment adherence. While cerebral blood flow (CBF) plays a crucial role in the development of various diseases, its relationship with sleep disorders remains uncertain. This observational study focuses on possible correlations between CBF and poor subjective sleep quality in MMT patients. Methods A total of 75 participants with a history of MMT were recruited and assessed using pseudo-continuous arterial spin labeling magnetic resonance imaging to determine CBF. A LAASO regression model was employed to identify the region of interest (ROI) most associated with sleep disturbance. The association between the CBF of the ROI and the Pittsburgh Sleep Quality Index (PSQI) was examined using regression analyses. Age, gender, BMI, history of hypertension, diabetes, hyperlipidemia, and methadone withdrawal were included as covariates. Results Among MMT patients with poor subjective sleep quality, significantly higher CBF was observed in the right paracentral lobule (56.1057 ± 11.1624 ml/100 g/min, p = 0.044), right cerebelum_3 (56.6723 ± 15.3139 ml/100 g/min, p = 0.026), right caudate nucleus (48.9168 ± 6.9910 ml/100 g/min, p = 0.009), and left caudate nucleus (47.6207 ± 6.1374 ml/100 g/min, p = 0.006). Furthermore, a positive correlation was found between CBF in the right paracentral lobule and the total PSQI score (β = 0.1135, p = 0.0323), with the association remaining significant even after adjustment for covariates (β = 0.1276, p = 0.0405). Conclusion MMT patients with poor subjective sleep quality exhibited significantly altered CBF in multiple brain regions. The association between increased CBF in the right paracentral lobule and subjective sleep quality in MMT patients could be crucial in understanding sleep disorders in individuals undergoing MMT. Clinical trial registration https://www.chictr.org.cn/, identifier: ChiCTR2100051931.